2015
DOI: 10.1103/physrevlett.115.022001
|View full text |Cite
|
Sign up to set email alerts
|

Could theX(3915)and theX(3930)Be the Same Tensor State?

Abstract: By using a combined amplitude analysis of the γγ→DD̅ and γγ→J/ψω data, we demonstrate that the X(3915), which is quoted as a J(PC)=0(++) state in the Particle Data Group table, is favored by the data to be a J(PC)=2(++) state appearing in both channels, which means that the X(3915) and the X(3930) can be regarded as the same J(PC)=2(++) state. Meanwhile, the data also prefer a large helicity-0 contribution of this tensor resonance to the amplitudes instead of the helicity-2 dominance assumed by BABAR, which ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 26 publications
6
59
0
Order By: Relevance
“…[821] combined the analysis for the amplitude and the angular distribution of the γγ → DD and γγ → J/ψω data from BaBar [154,152]. They found that the assignment of 2 ++ to the X(3915) was more consistent with the data.…”
Section: X(3915)mentioning
confidence: 96%
“…[821] combined the analysis for the amplitude and the angular distribution of the γγ → DD and γγ → J/ψω data from BaBar [154,152]. They found that the assignment of 2 ++ to the X(3915) was more consistent with the data.…”
Section: X(3915)mentioning
confidence: 96%
“…[5], presented in Ref. [12], shows that the 2 ++ assignment becomes possible if the λ = 2 assumption is abandoned. As a result of these considerations, the X(3915) is no longer identified as the χ c0 (2P ) in the 2016 PDG tables [13].…”
Section: Introductionmentioning
confidence: 99%
“…Also its width should be significantly larger than Γ χ c2 (2P) . More recently, Zhou et al [51] argued that what is dubbed X(3915) is the χ c2 (2P) state already known, and just like [49] suggest that a broader state is hiding in the experiment data. More recently Belle [52] have observed a state with mass M = 3862 +26+40 −32−13 MeV and with a width of Γ = 201 +154+88 −067−82 MeV.…”
Section: Charmonium-like States From Lattice Qcdmentioning
confidence: 99%